Solve ( D3 – 3DD′2+2D′3 )Z = e2x – y
Given "(D^{3}-3DD'^{2*}+2D'^{3})z=e^{2x-y}"
Put D=m and D'=1
Auxiliary equation is;
m3-3m+2=0
(m-1)(m2+m-2)=0
(m-1)(m-1)(m+2)=0
m=1, 1, -2
C.F=f1(y+x)+xf2(y+x)+f3(y-2x)
For particular integral,
"P.I=\\frac{1}{(D^{3}-3DD'^{2*}+2D'^{3})}e^{2x-y}"
Put D=2, D'=-1
"P.I=\\frac{1}{(2^{3}-3(2)(-1)^{2*}+2(-1)^{3})}e^{2x-y}"
"=\\frac{1}{8-6-2}e^{2x-y}"
On putting D=2 and D'=-1 in the denominator,it became zero.
Since the denominator becomes zero, we differentiate it with respect to D and multiply by x, we get
"P.I=\\frac{x}{\\frac{d}{dD}(D^{3}-3DD'^{2*}+2D'^{3})}e^{2x-y}"
"=\\frac{x}{(3D^{2}-3D'^{2*}+0)}e^{2x-y}"
"=x\\frac{1}{3D^{2}-3D'^{2}}e^{2x-y}"
Now out D=2 ,D'=-1
"=x\\frac{1}{3(2)^{2}-3(-1)^{2}}e^{2x-y}"
"=x\\frac{1}{12-3}e^{2x-y}"
P.I="\\frac{x}{9}e^{2x-y}"
So the solution becomes,
z=C.F+P.I
"=f_1(y+x)+xf_2(y+x)+f_3(y-2x)+\\frac{1}{9}xe^{2x-y}"
Comments
Leave a comment